Accountability Practice Based On Define Component Among Guidance And Counseling Teachers In Students At Risk Of Dropping Out Intervention Program - Moshidi, Nurulaini; Jusoh, Ahmad Jazimin (The journal of contemporary issues in business and government, 2021)
Students at risk of dropping out intervention program (PIMBC) are an initiative of the Ministry of Education Malaysia (MOE) in addressing the issue of students at risk of dropout. Guidance and Counseling Teachers (GBK) are responsible for planning and implementing this program. Therefore, GBK accountability practices through the define component should be identified in the implementation of PIMBC to achieve program effectiveness. A survey study used to review the level of accountability practices based on gender, duration of service and school location. This study involved 395 GBK people who teach in national secondary schools. Descriptive analysis and inference analysis involving t-test and One-way ANOVA test is used in data analysis. The findings of the study showed that the mean for the define component was 4.03 while the t-test showed that there was a significant difference between the genders. On the other hand, for the duration of service and school location analyzed using one-way ANOVA showed no significant difference. The define component is the basis for GBK in program implementation and is able to influence efforts to achieve the program objectives.